Molecular Basis for Mucolytic Therapy - Bonnie Dasgupta; Malcolm King (Canadian Respiratory Journal)
Airway mucus is a complex, viscoelastic gel that has a three-dimensional structure. It is composed of water, mucous glycoproteins, low molecular weight ions, proteins and lipids. The three-dimensional structure of the mucous gel depends on a number of forms of bonding, such as ionic bonds and disulphide bridges. Airway obstruction in cystic fibrosis (CF) lung disease is accompanied by the accumulation of thick and viscous secretions resulting from chronic infection and inflammation, promoting recurrent exacerbations. The normal, free-flow ing airway mucus becomes thick and purulent in patients suffering from CF lung disease. Therefore, current approaches to the treatment of CF include strategics for changing the physical properties of pulmonary secretions with the goal of improving airway clearance. Some of the same strategies may be applicable in the larger group of patients with chronic obstructive airway diseases, including bronchiectasis and chronic obstructive pulmonary disease. This paper reviews various approaches to mucolysis based on the molecular nature of crosslinking and bonding in mucin gels. A brief review of the structure and biochemistry of airway mucus is followed by a discussion of the various physical and biochemical approaches to mucolysis. Seven representative mucotropic modalities are presented: N-acetylcysteine; urea; hypertonic saline; recombinant human DNase; gelsolin; oscillation; and surfactants. Each of these mucotropic modalities acts on a different component within the mucous gel. Finally, the possibilities of mucolytic synergism among these various agents are conside red.